2021
DOI: 10.3233/blc-201528
|View full text |Cite
|
Sign up to set email alerts
|

“Picture this”- Patients’ Drawings of Non-Muscle Invasive Bladder Cancer: A Novel Method to Help Understand How Patients Perceive Their Condition

Abstract: BACKGROUND: There is a paucity of data regarding patient experiences of living with non-muscle-invasive bladder cancer (NMIBC). OBJECTIVES: To investigate patients’ beliefs about NMIBC utilising both a well-established verbal/linguistic method, the Brief Illness Perception Questionnaire (B-IPQ) in addition to a novel visual/perceptual method, that is, asking patients to draw their bladder as it is now and as they perceive it will be in the future. METHODS: Cross-sectional study of patients with NMIBC. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
2
1
0
Order By: Relevance
“…Many of those interviewed referred to the physical aspects associated with NMIBC and appraised themselves currently as ‘normal’ and ‘healthy’. This is commensurate with a previous study in NMIBC which found that patients tended to conceptualise their bladders in disease-focused ways, either with or without tumours (Richards et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Many of those interviewed referred to the physical aspects associated with NMIBC and appraised themselves currently as ‘normal’ and ‘healthy’. This is commensurate with a previous study in NMIBC which found that patients tended to conceptualise their bladders in disease-focused ways, either with or without tumours (Richards et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Recent quantitative research studies have yielded findings which have demonstrated the burden on bladder cancer patients’ quality of life and psychological wellbeing at all stages of the illness (Brisbane et al, 2019; Jung et al, 2021; Jung et al, 2020; Nayak et al, 2021; Pham et al, 2019; Richards et al, 2021; Smith et al, 2018; Vartolomeia et al, 2018). One recent population-based study showed individuals with NMIBC to have self-reported elevated levels of post-traumatic stress disorder symptoms, and it is suggested that the ongoing deleterious experiences of invasive cystoscopy procedures and/or invasive treatments for NMIBC patients may be related to continuing psychological distress for this group (Jung et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Richards H L et al. believed that FCR gradually decreased, which was consistent with the research findings ( 17 , 18 ). This may be when facing traumatic events, high-level cognition helps patients rebuild resources destroyed by the crisis.…”
Section: Discussionsupporting
confidence: 80%